Accuracy of a smartphone-based orthodontic treatment–monitoring application: A pilot study - Moylan, Heather B.; Carrico, Caroline K.; Lindauer, Steven J.; Tüfekçi, Eser (The Angle orthodontist, 2019)
To investigate the reliability and accuracy of a monitoring system in patients undergoing orthodontic treatment with a rapid maxillary expander. Specifically, the amount of tooth movement calculated by the software was compared with the actual measurements taken on plaster models obtained during an in-office visit. Patients took intraoral video scans using the monitoring software's smartphone application (Dental Monitoring, Paris, France), immediately followed by impressions for plaster models. Intercanine and intermolar width measurements were calculated by the software and compared with those made on the plaster models. Data were analyzed using two one-sided -tests for equivalence with equivalence bounds of ±0.5 mm. The significance level was set at .05. Thirty sets of measurements were compared. The intercanine and intermolar measurement differences were on average 0.17 mm and -0.02 mm, respectively, and were deemed equivalent. The monitoring software seems to provide an accurate assessment of linear tooth movements.